Multiterritorial strokes in the setting of spontaneous heparin-induced thrombocytopaenia syndrome. Issue 2 (28th February 2022) - Kwan, Christopher; Reimers, Jon; o'Gorman, Cullen; Bird, Robert; Brown, Helen
Abstract : We present a case study of a 38-year-old man who developed arterial and venous thrombi, resulting in multiterritorial strokes, a pulmonary embolus and a cerebral venous sinus thrombosis in the setting of spontaneous heparin-induced thrombocytopaenia syndrome.